(untitled) - Brownlee, W. Elliot (New York, 1974)
About a problem in political economy; taxation and captital information; the impact on Wisconsin frowth; progressives, manufactures and rhe adoption of income taxation ...
Keywords: Income tax,Thuế thu nhập